2017
DOI: 10.1021/acs.joc.7b02598
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Coupling of Acyl Chlorides with gem-Difluorinated Organozinc Reagents via Acyl Dithiocarbamates

Abstract: A cross-coupling of acyl chlorides with gem-difluorinated organozinc reagents affording difluorinated ketones is described. In the reaction, acyl chlorides are first treated with potassium dithiocarbamate to generate S-acyl dithiocarbamates, which couple with organozincs in the presence of a copper(I) catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…This approach has been further extended to the synthesis of technologically important ternary and quaternary sul- Copper dithiocarbamates have not found widespread use in homogeneous catalysis, despite having many of the attributes associated with good catalysts such as a range of accessible oxidation states and coordinative unsaturation. While the reaction discussed above is formally catalytic, the amounts of copper used are near to stoichiometric; nevertheless, there soon followed a range of related transformations in which much smaller amounts of copper were utilised either in the presence of dithiocarbamates [313,314] or thiuram disulfides [315][316][317][318]. By way of example, Bolm and co-workers have reported that Cu 2 O is an efficient catalyst for the formation of aryl dithiocarbamates from the coupling of thiuram disulfides and aryl iodides [315].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been further extended to the synthesis of technologically important ternary and quaternary sul- Copper dithiocarbamates have not found widespread use in homogeneous catalysis, despite having many of the attributes associated with good catalysts such as a range of accessible oxidation states and coordinative unsaturation. While the reaction discussed above is formally catalytic, the amounts of copper used are near to stoichiometric; nevertheless, there soon followed a range of related transformations in which much smaller amounts of copper were utilised either in the presence of dithiocarbamates [313,314] or thiuram disulfides [315][316][317][318]. By way of example, Bolm and co-workers have reported that Cu 2 O is an efficient catalyst for the formation of aryl dithiocarbamates from the coupling of thiuram disulfides and aryl iodides [315].…”
Section: Discussionmentioning
confidence: 99%
“…Existing methodologies for the construction of Ar–CF 2 –R linkages require reagents that are toxic, explosive, and of limited scope (Figure b) . The most common retrosynthetic disconnection is at the C–F bonds of the CF 2 unit through ketone deoxyfluorination using trifluorosulfuranes (e.g., DAST; Et 2 NSF 3 ) and radical fluorination of C–H bonds .…”
mentioning
confidence: 99%
“…Meanwhile, the group of Dilman [184] developed a method for the synthesis of difluorinated ketones with gem -difluorinated organozinc reagents (Scheme 110). Firstly, acyl chlorides reacted with potassium dithiocarbamate to generate S -acyl dithiocarbamates.…”
Section: Reviewmentioning
confidence: 99%